Human Rights and Cultural Diversity : Core Issues and Cases - Fagan, Andrew (Textbooks in Global Justice and Human Rights : TGJHR, 2022)
A student guide to reconciling human rights with cultural difference, using political philosophy and real-life case studiesHow can universal human rights be reconciled with respect for wide cultural differences? This textbook introduces the core issues for students and addresses them through an interdisciplinary analysis of key case studies. Throughout the book, an alternative philosophical framework is offered as a model through which universalism and difference can be reconciled into a single global vision.Key FeaturesCombines the theory and application of human rights to provide practical help for students and course leadersKey case studies examine the rights of women, ethnic and national minorities, indigenous peoples and religious communitiesAddresses a broad range of on-going political struggles and issues, including FGM, LGBT rights, freedom of speech and the rights of indigenous peoplesOutlines a new human rights-based philosophical perspective that enables students to understand human rights within culturally diverse environmentsHelpful student features include:Core questions: each chapter starts with 10 core questions, which students are invited to answer as they read to put what they learn into practiceFurther reading: every chapter ends with suggestions for further reading, to help students deepen their study in particular areasTwo-colour layout: blue text boxes and headings draw your attention to important information and make the book easier to read